A host–guest interaction activated Bobbitt oxidant for highly efficient oxidation of alcohols. Issue 92 (1st November 2022) - Wu, Jinyang; Luo, Youran; Chen, Lingxuan; Sun, Xuan; Chen, Xinnan; Qin, Song; Feng, Wen; Li, Xiaowei; Yuan, Lihua
Abstract : Host–guest complexation using hydrogen-bonded macrocycles was found to enable activation of the Bobbitt oxidant reagent, which greatly facilitates the highly efficient oxidation of unactivated primary alcohols. Abstract : Host–guest complexation using hydrogen-bonded macrocycles was found to enable activation of the Bobbitt oxidant reagent, which greatly facilitates the highly efficient oxidation of unactivated primary alcohols. This work provides a complementary approach to the activation of Bobbitt's salt with shape-persistent macrocycles in supramolecular catalysis.